Discourses of Southeast Asia
XIV, 254 p. 87 illus., 14 illus. in color.
Keywords: Discourses of Southeast Asia presents the latest Southeast Asian research in Systemic Functional Linguistics (SFL). SFL provides a sophisticated social semiotic architecture for exploring meaning in languages and texts in the context of Southeast Asia. This edited volume examines the ideational, interpersonal and textual metafunctions in the domains of education, media, translation and language typology. It applies SFL in text analysis so as to be relevant to theory, research and professional practice. This book brings together 12 original chapters by both seasoned and emerging scholars. Their chapters study the ‘native’ languages of Southeast Asia: Indonesian, Malay, Tagalog, Thai and Vietnamese, and relatively newer languages in Southeast Asia: English and Mandarin. The chapters analyze a variety of texts, namely advertisements, classroom interactions, corporate reports, dramas, interviews, media reports, narratives, novels, textbooks and video clips. This volume captures the exciting and productive state of the art of SFL in Southeast Asia. It will be of particular interest to scholars trying to understand the application of SFL in this region.